The Dynamic Response of the Green Stock Market to External Economic Policy Uncertainty: The Case of Indonesia - Rahmi, Nanda; Samsudin, Hazman; Ahmat, Nizam (International Journal of Energy Economics and Policy, 2025)
This study analyzes the effects of economic policy uncertainty and external shocks on the Indonesian green stock market. This study uses secondary data from January 2010 to December 2023, covering a sample size of 168 months, and uses the ARDL model to estimate the research framework. The study findings reveal that, in the short term, the exchange rate has a significant effect on the green stock market, while economic policy uncertainty, including domestic economic policy uncertainty, does not affect the green stock market. This suggests that the green stock market is less susceptible to external market sentiment and tends to be more stable in the short term. In addition, there is a difference in the effects of the exchange rate and oil prices. Again, similar results are also revealed in the long term, which sees only the exchange rate affecting the green stock market. This suggests that investment in the Indonesian green stock market is based on a paradigm shift towards more sustainable economic practices where other external sentiments may not significantly affect investment decisions. The implications of these findings are important for policymakers and investors to consider green stocks, which tend to be more stable than conventional stocks.